Research on the Construction of Digital Standard Contracts for Artificial Intelligence Data Training - Ren, Qiuhui; Fu, Xiaohua (Asia Pacific Economic and Management Review, 2026)
Based on the analysis and comparative study of domestic and foreign literature, this paper focuses on the legal regulatory issues arising from the process of artificial intelligence (AI) data training. It aims to address the inherent contradictions between machine learning models and the technical characteristics of traditional legal norms, the lack of algorithmic transparency, and the identification of data ownership by constructing digital standard contracts. Corresponding development suggestions are put forward from three aspects: establishing a dynamic update mechanism for contracts, standardizing transnational data training cooperation, and deepening the legal effect of contract execution results.